Tuning a first order plus time delay process with cascade control - Chen, Siew Chin, 1989-, author; Kamarul Asri, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - Universiti Teknologi Malaysia, 2012